Evaluation of the neuroprotective effect of ketoprofen on rats submitted to permanent focal brain ischemia Avaliação do efeito neuroprotetor do cetoprofeno em ratos submetidos à isquemia cerebral focal permanente - Manoel Nunes da Silva; Benedicto Oscar Colli; Norberto Cysne Coimbra; Joaquim Coutinho Netto (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To study the neurobehavioral, biochemical and histopathological consequences of permanent focal brain ischemia, and the putative neuroprotective action of ketoprofen. METHOD: One-hundred-and-three Wistar rats divided into groups A and B were respectively submitted to 48 hours and 15 days of ischemia. Each group was divided into 4 subgroups: ischemic not treated, ischemic treated, sham not treated, and sham treated. Ischemic animals had the left middle cerebral artery coagulated. Ketoprofen was administered to treated subgroups 15 minutes before arterial coagulation (manipulation in the sham group). RESULTS: Exploratory activity and defecation were reduced in all ischemic animals in the first postoperative days and constant histopathological changes were observed in each group. The total brain glutamate levels were higher in treated animals 48 hours after surgery. CONCLUSION: No clear parallelism among behavioral, biochemical and histopathological findings was observed. Ketoprofen demonstrated no neuroprotective effect on the behavioral or histopathological aspects of focal permanent brain ischemia. OBJETIVO: Estudar as conseqüências comportamentais, bioquímicas e histopatológicas da isquemia cerebral focal permanente e o possível efeito neuroprotetor do cetoprofeno. MÉTODO: Foram utilizados 103 ratos Wistar, divididos em grupos A e B, submetidos, respectivamente, a 48 horas e a 15 dias de isquemia. Cada grupo foi dividido em 4 subgrupos: isquêmico não tratado; isquêmico tratado; sham não tratado; sham tratado. Nos animais isquêmicos foi coagulada a artéria cerebral média esquerda. Os subgrupos tratados receberam cetoprofeno 15 minutos antes da oclusão ou manipulação arterial. RESULTADOS: Os animais isquêmicos reduziram a atividade exploratória e as evacuações nos primeiros dias pós-operatórios e mostraram alterações histopatológicas constantes em cada grupo. As concentrações do glutamato total 48 horas após a cirurgia foram maiores nos animais tratados. CONCLUSÃO: Não houve um paralelismo entre os achados comportamentais, bioquímicos e histopatológicos. O cetoprofeno não apresentou efeito protetor contra isquemia cerebral focal permanente, nos aspectos comportamentais e histopatológicos.